Roles of N-Methyl-D-Aspartate Receptors (NMDARs) in Epilepsy - Chen, Shuang; Xu, Da; Fan, Liu; Fang, Zhi; Wang, Xiufeng; Li, Man (Frontiers in Molecular Neuroscience, 2022)
Epilepsy is one of the most common neurological disorders characterized by recurrent seizures. The mechanism of epilepsy remains unclear and previous studies suggest that N-methyl-D-aspartate receptors (NMDARs) play an important role in abnormal discharges, nerve conduction, neuron injury and inflammation, thereby may participate in epileptogenesis. NMDARs belong to a family of ionotropic glutamate receptors that play essential roles in excitatory neurotransmission and synaptic plasticity in the mammalian CNS. Despite numerous studies focusing on the role of NMDAR in epilepsy, the relationship appeared to be elusive. In this article, we reviewed the regulation of NMDAR and possible mechanisms of NMDAR in epilepsy and in respect of onset, development and treatment, trying to provide more evidence for future studies.